Problems in price theory - Meyer, Robert A. (Boston : Houghton Mifflin Co., 1973)
This is a work book that lays focus on prices, microeconomics and equilibrium.
kjo 18/01/2019
Loans
Keywords: Microeconomics; Equilibrium (Economics); Prices